2015
DOI: 10.1111/acer.12591
|View full text |Cite
|
Sign up to set email alerts
|

Binge‐Like Consumption of Ethanol and Other Salient Reinforcers is Blocked by Orexin‐1 Receptor Inhibition and Leads to a Reduction of Hypothalamic Orexin Immunoreactivity

Abstract: Background Orexin (OX) neurons originating in the lateral hypothalamus (LH) are ideally positioned to modulate reward processing as they form connections with several key brain regions known to be involved in the reward pathway. Consistent with these findings, a growing number of studies have implicated the OX system in modulating the rewarding properties of several drugs of abuse, including ethanol (EtOH). However, the role of the OX system in excessive binge-like EtOH intake remains relatively unexplored. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 39 publications
6
54
2
Order By: Relevance
“…The models include either the two-bottle choice procedure that provides 24-hour access to water plus 10-20% alcohol for 3 days per week (Carnicella, Ron, & Barak, 2014) or the “drinking in the dark” model that replaces the water bottle with a bottle of 20% alcohol for 2 to 4 hours (Thiele, Crabbe, & Boehm, 2014). With these intermittent access paradigms, peripheral administration of the OX1R antagonists SB-334867 and GSK1059865 are found to reduce alcohol intake and preference in both rats and mice (Lopez, Moorman, Aston-Jones, & Becker, 2016; Moorman & Aston-Jones, 2009; Olney, Navarro, & Thiele, 2015). Similarly, SB-334867 inhibits the lower-level drinking obtained from ad libitum home cage access (Anderson, Becker, Adams, Jesudason, & Rorick-Kehn, 2014).…”
Section: Role Of Orexin/hypocretin In Non-homeostatic Intakementioning
confidence: 99%
See 1 more Smart Citation
“…The models include either the two-bottle choice procedure that provides 24-hour access to water plus 10-20% alcohol for 3 days per week (Carnicella, Ron, & Barak, 2014) or the “drinking in the dark” model that replaces the water bottle with a bottle of 20% alcohol for 2 to 4 hours (Thiele, Crabbe, & Boehm, 2014). With these intermittent access paradigms, peripheral administration of the OX1R antagonists SB-334867 and GSK1059865 are found to reduce alcohol intake and preference in both rats and mice (Lopez, Moorman, Aston-Jones, & Becker, 2016; Moorman & Aston-Jones, 2009; Olney, Navarro, & Thiele, 2015). Similarly, SB-334867 inhibits the lower-level drinking obtained from ad libitum home cage access (Anderson, Becker, Adams, Jesudason, & Rorick-Kehn, 2014).…”
Section: Role Of Orexin/hypocretin In Non-homeostatic Intakementioning
confidence: 99%
“…While OX activity is inhibited by acute alcohol at a very high dose that promotes sleep (Sharma, Sahota, & Thakkar, 2014), similar to its inhibition after a physiological rise in glucose levels (Burdakov et al, 2005), gene expression and peptide levels of OX are significantly increased by alcohol administered at lower doses (Morganstern et al, 2010). Similarly, in response to voluntary intake, OX gene expression is stimulated during the first 30 minutes following the start of intake (Barson et al, 2015; Lawrence et al, 2006; Sterling, Karatayev, Chang, Algava, & Leibowitz, 2015) but is subsequently unaffected or reduced along with OX peptide levels over the next several hours (Morganstern et al, 2010; Olney et al, 2015, 2017). This time-dependent shift in the effects of alcohol on OX, a stimulation followed by a suppression, may help to explain why individuals engage in alcohol binge sessions of a discrete duration (Carnicella et al, 2014), with drinking continuing until blood alcohol levels are sufficiently high to alter behavior and then ceasing until blood levels have significantly declined.…”
Section: Role Of Orexin/hypocretin In Non-homeostatic Intakementioning
confidence: 99%
“…In particular, ORX plays an important function in driving the seeking of drugs of abuse, including alcohol (Baimel et al, 2015; Brown and Lawrence, 2013; Lawrence, 2010; Mahler et al, 2012). The orexin peptide is increased in some animal models of alcohol drinking and decreased in others (Lawrence et al, 2006; Morganstern et al, 2010; Olney et al, 2015), and ORX neurons are activated following reinstatement of alcohol seeking (Dayas et al, 2008; Hamlin et al, 2007). Antagonism of the OX1R decreases alcohol drinking, notably in higher-drinking alcohol-preferring animals (Anderson et al, 2014; Moorman and Aston-Jones, 2009; Olney et al, 2015), decreases self-administration, progressive-ratio, and reinstatement of alcohol seeking (Jupp et al, 2011; Lawrence et al, 2006; Martin-Fardon and Weiss, 2014a; Richards et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Second, consistent with a role for OX in impulsivity-like behaviors, the OXr1 antagonist SB-334867 peripherally administered regulated impulsive behavior under both baseline and cocaine-stimulated conditions in a dynorphin-sensitive manner in food-restricted rats, as measured by premature responses exhibited in the 5-choice serial reaction time task (5-CSRTT) (Muschamp et al, 2014). Third, recent studies have highlighted the role of OX system in binge-like consumption of rewarding stimulus (sucrose, saccharin and ethanol) in non-dependent animals (Alcaraz-Iborra et al, 2014;Anderson et al, 2014;Olney et al, 2015) as measured by the Drinking in the Dark (DID) paradigm, a wellestablished procedure to reproduce pre-dependent episodes of human binge consumption patterns in mice (Thiele and Navarro, 2014). Thus, the OXr1 antagonist SB-334867 reduced sucrose, saccharin (AlcarazIborra et al, 2014) and ethanol (Anderson et al, 2014;Olney et al, 2015) binge-like drinking when administered peripherally and ethanol binge-like drinking when centrally infused (Carvajal et al, 2015) in non-deprived mice.…”
Section: Oxr1 Signaling Modulates Impulsivity and Binge-like Consumptmentioning
confidence: 99%
“…Third, recent studies have highlighted the role of OX system in binge-like consumption of rewarding stimulus (sucrose, saccharin and ethanol) in non-dependent animals (Alcaraz-Iborra et al, 2014;Anderson et al, 2014;Olney et al, 2015) as measured by the Drinking in the Dark (DID) paradigm, a wellestablished procedure to reproduce pre-dependent episodes of human binge consumption patterns in mice (Thiele and Navarro, 2014). Thus, the OXr1 antagonist SB-334867 reduced sucrose, saccharin (AlcarazIborra et al, 2014) and ethanol (Anderson et al, 2014;Olney et al, 2015) binge-like drinking when administered peripherally and ethanol binge-like drinking when centrally infused (Carvajal et al, 2015) in non-deprived mice. Moreover, additional to pharmacological studies, in our lab we observed that following 4 repetitive episodes of bingelike consumption of both sucrose and saccharin, OX mRNA expression was dampened in the lateral hypothalamus (LH), suggesting a shortterm adaptive and compensatory reduction of OX synthesis in response to binge-like consumption (Alcaraz-Iborra et al, 2014).…”
Section: Oxr1 Signaling Modulates Impulsivity and Binge-like Consumptmentioning
confidence: 99%